Implementasi Alat Electric Fertilizer Untuk Mempengaruhi Pertumbuhan Tanaman Jagung Manis (Zea mays L.) - Raditya Putra Suhendra; Diah Arie W. K; Nadhifah Al Indis (Jurnal Ilmiah Sistem Informasi, 2022)
Electric current inserted to the soil media to stimulate plant growth is called electric fertilizer (EF). There are two types of plant fertilization methods, physical & chemical fertilization (synthetic chemistry and organic chemistry). EF is an alternative physical fertilizer that can be used for enhance plant growth beside chemical and biological fertilizer. Using EF can decrease inorganic or agrochemical input which often lead to soil degradation and high production cost in the implementation. This research aims to design EF apparatus to exerting DC electric current and voltage to the soil using electrode plate as a probe to stimulate sweet corn (Zea mays L.) growth and to design an automatic irrigation system using soil moisture sensor. This research also examines the effect of electric input on sweet corn growth. The application of EF with 12V DC (in variable C) which observed for five days show the highest measurements results, but the control variable (A) had a more stable increase in plant height. This research show that EF can stimulate sweet corn growth when it set under appropriate time and electric voltage condition. Variables C and A had the similar weigh, with a difference of 0,02 gram.